AN ANALYSIS OF FIGURATIVE LANGUAGE FOUND IN KATY PERRYâ€™S SONG ENTITLED â€œFIREWORKâ€ - Putu Ratna, Arditami (Lingua Scientia, 2017)
The existence of figurative language as a way of conveying utterance other than its ordinary way helps the song writer in composing and producing beautiful songs. By using figurative language, the singer could deliver the messages existed in a song in a brief yet meaningful way. Furthermore a song entitled â€œFireworkâ€ attracts the researcherâ€™s attention in doing analysis about the types of figurative language. This study then focuses on analyzing the types of figurative language and its meaning found in the song lyric entitled â€œFireworkâ€ by Katy Perry. The aims of the study are to identify and describe the meaning of the types of figurative language used in the song â€œFireworkâ€. This study implements descriptive qualitative method. The data of the study is the song lyric entitled â€œFireworkâ€ by Katy Perry which is taken from azlyrics.com. This study applies study documentation as the method in collecting the data. The result of data analysis shows that there are six types of figurative language found in the song lyric entitled â€œFireworkâ€ by Katy Perry. They are symbol, hyperbole, simile, personification, metaphor, and paradox. Furthermore, the meaning of these types of figurative language is also described by the researcher.